Comparative Analysis Of Radiological And Dental Age With The Chronological Age In Sports Individuals (Journal of Forensic Medicine & Toxicology, 2026)
Introduction: Age is a primary identification character of an individual with great medicolegal importance. Age estimation in Forensic Medicine has always been challenging with the changing time and rapid evolution of scientific methods of estimation. It is crucial in certain fields like education, sports and other civil and crim inal purposes. For participation in sports at national and international level, age verification is mandatory for maintaining fair play, adhere to international standards, prevent fraud etc. But the question is, how accurate can the age of an individual be identified using radiological and dental examination? Aim: To compare the chronological age of a person with radiologically estimated age from examination of ossification centres of bones and dental age from physical examination. Materials & Methodology: The study was performed on 160 football players who visited to our department in November, 2024, for age verification before participating in a National Level football competition held in Chandigarh. The age range of the participants was from 12 to 16 years, competing in under 18 category. Each participant’s height, weight, physical & dental examination, and x rays for bone ossification centres of the shoulder joint, elbow joint, wrist joint and hip joint were performed using weighing machine, stadiometer, x ray machine and analysed. Results: The mean height of the participants was 167.84 cm and mean weight was 57.76 kgs. The frequency percentage of agreement between chronological age and dental age was 63%, whereas that between chrono logical age and radiological age, was 3%. The mean age of participants was 15.1875 with SD of +/-0.870. On dental examination, the calculated mean age was 15.1875 with SD of +/- 0.0623. On radiological examination, the calculated mean age was 10.7501 with SD of +/- 0.0233 Conclusion: In our study, we have observed great difference between dental age, radiological bone age with chronological age. Possible reasons could be less sample size and effect of hormones on radiological bone age in sports individuals. Standard methods for age verification in sports persons should be followed to remove method bias.
Keywords: Age Estimation; Sports Medicine; Radiological Age; Dental Age; Epiphyseal Fusion